Heteronuclear NMR Spectroscopy as a Surface‐Selective Technique: A Unique Look at the Hydroxyl Groups of γ‐Alumina. Issue 14 (6th March 2014) - Taoufik, Mostafa; Szeto, Kai C.; Merle, Nicolas; Rosal, Iker Del; Maron, Laurent; Trébosc, Julien; Tricot, Grégory; Gauvin, Régis M.; Delevoye, Laurent
Abstract The surface hydroxyl groups of γ‐alumina dehydroxylated at 500 °C were studied by a combination of one‐ and two‐dimensional homo‐ and heteronuclear 1H and 27Al NMR spectroscopy at high magnetic field. In particular, by harnessing 1H–27Al dipolar interactions, a high selectivity was achieved in unveiling the topology of the alumina surface. The terminal versus bridging character of the hydroxyl groups observed in the 1H magic‐angle spinning (MAS) NMR spectrum was demonstrated thanks to 1H–27Al RESPDOR (resonance‐echo saturation‐pulse double‐resonance). In a further step the hydroxyl groups were assigned to their aluminium neighbours thanks to a 1H‐27Al dipolar heteronuclear multiple quantum correlation (D‐HMQC), which was used to establish a first coordination map. Then, in combination with 1H–1H double quantum (DQ) MAS, these elements helped to reveal intimate structural features of the surface hydroxyls. Finally, the nature of a peculiar reactive hydroxyl group was demonstrated following this methodology in the case of CO2 reactivity with alumina.